Optimal target blood pressure in critically ill adult patients with vasodilatory shock: A systematic review and meta-analysis - Yoshimoto, Hidero; Fukui, Satoshi; Higashio, Koki; Endo, Akira; Takasu, Akira; Yamakawa, Kazuma (Frontiers in Physiology, 2022)
While the Surviving Sepsis Campaign guidelines recommend an initial target value of 65 mmHg as the mean arterial pressure (MAP) in patients with septic shock, the optimal MAP target for improving outcomes remains controversial. We performed a meta-analysis to evaluate the optimal MAP for patients with vasodilatory shock, which included three randomized controlled trials that recruited 3,357 patients. Between the lower (60–70 mmHg) and higher (>70 mmHg) MAP target groups, there was no significant difference in all-cause mortality (risk ratio [RR], 1.06; 95% confidence intervals [CI], 0.98–1.16) which was similar in patients with chronic hypertension (RR, 1.10; 95% CI, 0.98–1.24) and patients aged ≥ 65 years (RR, 1.10; 95% CI, 0.99–1.21). No significant difference in adverse events was observed between the different MAP groups (RR, 1.04; 95% CI, 0.87–1.24); however, supraventricular arrhythmia was significantly higher in the higher MAP group (RR, 1.73; 95% CI, 1.15–2.60). Renal replacement therapy was reduced in the higher MAP group of patients with chronic hypertension (RR, 0.83; 95% CI, 0.71–0.98). Though the higher MAP control did not improve the mortality rate, it may be beneficial in reducing renal replacement therapy in patients with chronic hypertension.